2019
DOI: 10.3390/ijerph16234738
|View full text |Cite
|
Sign up to set email alerts
|

Costs and Willingness to Pay for Pit Latrine Emptying Services in Kigali, Rwanda

Abstract: Kigali, Rwanda lacks a centralized sewer system, which leaves residents to choose between on-site options; the majority of residents in informal settlements use pit latrines as their primary form of sanitation. When their pits fill, the pits are either sealed, or emptied; emptying is often done by hand and then dumped in the environment, putting the residents and the broader population at risk of infectious disease outbreaks. In this paper, we used revealed and stated preference models to: (1) estimate the dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 18 publications
2
41
0
Order By: Relevance
“…In the case of Gasia Poa, we only compared stated and revealed WTP at higher price points, which may have limited our ability to detect significant differences (Fig 3B). Nevertheless, at market prices, stated and revealed demand for both types of emptying services was low-less than 20% of households were willing to pay full market prices ( Fig 3B and 3C); these results are comparable to a similar study in Rwanda that found only 15% of pits would be emptied at estimated prices that did not include subsidies [5].…”
Section: Study Summary and Key Findingssupporting
confidence: 66%
See 3 more Smart Citations
“…In the case of Gasia Poa, we only compared stated and revealed WTP at higher price points, which may have limited our ability to detect significant differences (Fig 3B). Nevertheless, at market prices, stated and revealed demand for both types of emptying services was low-less than 20% of households were willing to pay full market prices ( Fig 3B and 3C); these results are comparable to a similar study in Rwanda that found only 15% of pits would be emptied at estimated prices that did not include subsidies [5].…”
Section: Study Summary and Key Findingssupporting
confidence: 66%
“…We estimated annual emptying costs to be 50-95 USD per toilet, or 8-16 USD per household. For comparison, prior studies estimated that the annual costs of safe emptying services, in optimal scenarios with high market penetration, would amount to approximately 4-8 USD per household in Bangladesh [6] and 7 USD per household in Rwanda [5]. Our cost estimates for Kisumu are slightly higher than in these other settings, though extending safe emptying services to all Kisumu households may offer opportunities for economies of scale and reduce costs.…”
Section: Study Summary and Key Findingsmentioning
confidence: 66%
See 2 more Smart Citations
“…In Tanzania and Kenya, experimental trials found that <5% of rural households were willing to pay the market price for latrine slabs, though demand was much higher at discounted levels: approximately 90% of households in Kenya and 60% in Tanzania were willing to pay some amount for latrine slabs [ 7 , 8 ]. Similarly, previous studies have shown that WTP for safe latrine pit emptying services is substantially lower than market prices: household contributions only covered an estimated 47% of safe pit latrine emptying costs in rural Bangladesh [ 9 ], 40% of emptying costs in urban Rwanda [ 10 ], and 25–50% of emptying costs in urban Kenya [ 11 ]. This growing body of evidence indicates substantial differences between household demand and supply costs for improved sanitation products and services, which can be quantified as financial gaps [ 12 ].…”
Section: Introductionmentioning
confidence: 93%